Is there a part-time/ full-time pay differential in Australia?. (February 2015) - Preston, Alison; Yu, Serena
The incidence of part-time employment in Australia is high by international standards and the trend towards part-time work is on the rise. In this paper, we show that, on average, part-timers earn significantly less than full-timers. After controlling for human capital characteristics, the adjusted hourly earnings gap between men employed full-time and women employed part-time is equal to 22.5%. When comparing women only, the human capital adjusted part-time/full-time gap is equal to 8.9%. The latter falls to 1.1% when industry and occupation are controlled for, reflecting important segregation effects. These findings are consistent with international evidence. Consistent with other Australian studies, we also find that the part-time pay gap varies with casual status. In the female labour market, our human capital adjusted models show a part-time casual premium equal to 3.6% relative to the base group (women employed full-time on a non-casual basis).